The influence of higher learning environment and role model towards an entrepreneurial intention among TVET students / Rifhan Roslan, Nur Iliza Misnan and Dzulkarnain Musa - Roslan, Rifhan; Misnan, Nur Iliza; Musa, Dzulkarnain (Universiti Teknologi MARA, Perlis, 2020)
The Technical and Vocational Education and Training (TVET) field is part of the drive for national development. With the circumstances, the TVET institutions have taken steps towards creating future entrepreneurs as well as contributing to high-skilled employment. Thus, the study was conducted to examine several factors related to higher learning environment and role model as well as their relationship with entrepreneurship intentions among TVET students. The study was hypothesized and tested using three dimensions of TVET higher learning environment (entrepreneurship education, entrepreneurship activities and teaching and learning methods) and role model factors that influence students' entrepreneurial intention. The results from correlation analysis found that there was a relationship between all the independent variables; entrepreneurship activities, role models, entrepreneurship education and teaching and learning methods with entrepreneurial intentions. The overall results of the study act as an enlightenment for related parties in developing future entrepreneurship society for the development of the country.